2-(Alkylthio)-3-(Naphthalen-1-yl)Quinazolin-4(3H)-Ones: Ultrasonic Synthesis, DFT and Molecular Docking Aspects. (9th August 2022) - Mohammed, Farrhat F.; Hagar, Mohamad; Parveen, Shazia; Alnoman, Rua B.; Ahmed, Hoda A.; Ashry, El Sayed H. El; Rasheed, Hanaa A.
Abstract: 3-(Naphthalen-1-yl)-2-thioxo-2, 3-dihydroquinazolin-4(1 H )-one 1, and its S -alkylated products 2–6, were effectively synthesized under ultrasonic irradiation under greener reaction condition with lower amount of solvent and in shorter reaction time to afford higher yield of the targeted compounds. 1 H and 13 C NMR, %CHN and FT-IR confirmed the structure of the synthesized products. The theoretical DFT calculations were carried out to study the electronic effect of the S -alkylated group on the structural as well as the thermal parameters for the investigated compounds. Further, the partition coefficient and other molecular properties of compounds 1–6 and their molecular docking studies were carried out with the target protein VEGFR-2 to determine the specific binding preferences at the target site. Structure–activity relationship (SAR) was inferred for future optimization based on the performed docking studies.